ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PEMANEN KARET (HEVEA BRASILIENSIS) DI KSO PTPN III KEBUN KARANG INONG KECAMATAN RANTAU PEUREULAK KABUPATEN ACEH TIMUR - Nurhaliza Nurhaliza; Muhammad Jamil; Cut Gustiana (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims analyze the effect of age, education level, years of service (experience) and number of dependents on work productivity of rubber harvesting employees at KSO PTPN III Kebun Karang Inong. The method of determining the sample is using a sampling technique, namely Probability Sampling, as many as 42 respondents and conducting research consisting of 7 respondents using the Simple Random Sampling method. The data collected in this study are primary data and secondary data. The data analysis method used in this study is Multiple Linear Regression Analysis, using the Classical Assumption Test (Normality Test, Multicollinearity and Heteroscedasticity) and Hypothesis Testing (f test, t test and test). The results showed that simultaneously the influence of the independent variables (age, education level, years of service and number of dependents) on the dependent variable (employee work productivity). Partially, education level and years of service have a significant effect on work productivity, while age and number of dependents have no significant effect on work productivity.